Martha Desrumaux, une nécessité : transmettre l’histoire - Pierre Outteryck (Cahiers d’histoire)
Let’s open the Pantheon to the working world ! Martha Desrumaux, for a female worker in the Pantheon ! Here is the campaign of the Friends of Martha Desrumaux’s association. How, with what tools, by what process, can we highlight Martha’s DNA and bring together on a large scale, to build and succeed in this campaign ? Martha Desrumaux, has she been forgotten in history or forgotten by history ? Indeed, the question of the gaze, the ambitions of historical research is raised. How can we show the extraordinary path of this northern worker ? Martha, a textile worker, anchored among her comrades, is able to launch a modern and ever-present struggle : feminism in industrial companies, the place and essential role of women. A modern struggle ? Some doubt it. But the high school students that we met in Chambéry have, through their questions, given one of the keys : the commitments, the fight and the values that Martha has brought, have raised a passionate interest.